Compound feed for broiler geese - DUAN YUZHEN (2018)
The invention discloses a compound feed for broiler geese. The compound feed for the broiler geese is prepared from the following raw materials in parts by weight: 48 to 60 parts of corn, 15 to 32 parts of bean cake, 8 to 15 parts of shell powder, 10 to 20 parts of rhizoma fagopyri dibotryis, 1 to 3 parts of grape seed oil, 5 to 12 parts of silkworm chrysalis meal, 8 to 18 parts of sesame seed meal, 2 to 6 parts of clover, 1 to 3 parts of rhizoma cyperi powder, 5 to 9 parts of seaweed meal, 2 to 4 parts of calcium hydrophosphate, 0.8 to 1.6 parts of decavitamin, 3 to 7 parts of felon herb, 1 to 3 parts of rhizoma coptidis powder, 5 to 12 parts of carrot powder, 1 to 3 parts of phagostimulant, and 0.6 to 1.5 parts of table salt. According to the compound feed for the broiler geese providedby the invention, the broiler geese can be promoted to grow, the morbidity of the broiler geese is reduced, and the quality of geese meat is improved. 本发明公开了种肉鹅复合饲料，所述肉鹅复合饲料是由以下重量份的原料组成：玉米48-60份，豆饼15-32份，贝壳粉8-15份，金荞麦10-20份，葡萄